A arquitetura mítica da narrativa rosiana: as raízes do monomito na travessia heróica de Augusto Matraga - Pereira, Alexandre Gonçalves (2009)
The research investigates Guimarães Rosa s mythical speech through the construction of the mythical character, according to Campbell s model of the monomyth. The corpus adopted is the short story A Hora e Vez de Augusto Matraga. It also focuses the sources of the literary creation in which the author got his inspiration to conceive a character that although he symbolizes a man from Brazilian backlands, transcends the documental record, the ascension to the condition of mythical hero through the adventures and the search of the salvation of his soul. We started from the hypothesis of that the construction of the mythical character, according to the diagram of the monomyth, besides being an indelible features of identification of the myth in Rosa s fiction, also clarifies the importance of the metaphysical religious worries of the author about the conception of his work, because the hero of the monomyth shows, during his trajectory, features of rituals of initiation. The aspect of initiation of the trajectory of the mythological hero reveals the holy meaning of the myth of the hero: this one symbolizes the divine potential in human being who only can be developed due to a project of ascetic life and of a heroic ethos. Identifying the archetype of the mythological hero in creation of the character Augusto Matraga, according to the key of reading of the monomyth, we identify the meeting among myth, religion and literature in the work of an author who transcended the documental regionalism, as a result of the creation of the myth of the spiritual asceticism of a character in the heart of the backlands of the North of Minas Gerais